Managing commonly owned property according to the civil transactions system: A comparative study - Abdullah Mohammed Al-Ammari (International Journal of Law Research and Studies, 2026)
The study aims to identify the statutory and legal foundations governing the management of commonly owned property, determine the scope of co-owners’ powers and rights, and examine the role of the judiciary in resolving disputes arising from such management. The study employs a descriptive, inductive, and analytical approach. The descriptive approach is employed to describe private ownership and common ownership, while the inductive approach is used to collect and examine the various aspects related to the research topic and review the relevant literature and discussions. The analytical approach is applied through gathering legal facts and information, comparing them, and extracting the most significant rules and legal principles associated with the subject in order to assess their consistency with, or deviation from, general legal principles. This methodology serves the objectives of the study by identifying areas of convergence and divergence through the examination, analysis, and comparison of the legal provisions governing common ownership in both jurisdictions, while linking them to relevant Islamic jurisprudential opinions and established legal principles, with reference to practical applications whenever possible. The study addresses the concept of common ownership from linguistic, juristic, and legal perspectives, related terminology, the historical development of property rights, the sources of common ownership, the concept and characteristics of commonly owned property, the right of disposition therein, restrictions on its management, and the Shariah ruling concerning real rights in commonly owned property. It also examines the different forms of management of common property, namely ordinary management, extraordinary management, and preservation management. The first chapter discusses the provisions governing the management of commonly owned property under Saudi and UAE law, including the voting thresholds required for decisions relating to ordinary management, extraordinary management, and preservation management, as well as the mechanisms governing each form of management. The second chapter provides a comparative analytical study of the relevant provisions in both legal systems, highlighting points of similarity and difference and assessing the adequacy of these provisions in balancing the interests of co-owners and protecting their rights. This study concludes that both the Saudi Civil Transactions Law and the UAE Civil Transactions Law adopt the principle of binding majority decisions based on the value of ownership shares in matters of ordinary management, while requiring a qualified majority of three-quarters of the common property for decisions that exceed the scope of ordinary management. Both systems also recognize the judiciary as a fundamental safeguard for protecting the rights of dissenting co-owners. The study further finds that UAE law provides a special regulatory framework for family ownership, whereas the Saudi system adopts a more general approach while maintaining a clear classification of management categories. This study recommends strengthening the procedural regulation of common property management, more precisely defining the powers and responsibilities of the manager, and unifying certain legal procedures to reduce disputes, promote legal certainty, and ensure the optimal utilization of commonly owned property.